2011
DOI: 10.1158/1055-9965.epi-10-0698
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Genome-Wide Prostate Cancer Associations in Men of African Descent

Abstract: Background Genome-wide association studies (GWAS) have identified numerous prostate cancer susceptibility alleles, but these loci have been identified primarily in men of European descent. There is limited information about the role of these loci in men of African descent. Methods We identified 7,788 prostate cancer cases and controls with genotype data for 47 GWAS-identified loci. Results We identified significant associations for SNP rs10486567 at JAZF1, rs10993994 at MSMB, rs12418451 and rs7931342 at 11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 54 publications
11
82
0
2
Order By: Relevance
“…4,19 Other replication studies have also confirmed an association between rs10993994 and increased PCa risk. 18,20,21 Our observations (Table 3) suggest that increased PCa risk associated with the minor allele (T) of rs10993994 is probably inherited in a recessive manner. Taken together, these findings support further exploratory studies using rs10993994 as a predictive genetic marker of PCa susceptibility in programs such as targeted screening for PCa in high-risk individuals or personalized PCa risk assessment.…”
Section: Discussionmentioning
confidence: 82%
“…4,19 Other replication studies have also confirmed an association between rs10993994 and increased PCa risk. 18,20,21 Our observations (Table 3) suggest that increased PCa risk associated with the minor allele (T) of rs10993994 is probably inherited in a recessive manner. Taken together, these findings support further exploratory studies using rs10993994 as a predictive genetic marker of PCa susceptibility in programs such as targeted screening for PCa in high-risk individuals or personalized PCa risk assessment.…”
Section: Discussionmentioning
confidence: 82%
“…As of this writing, one PCa GWAS has been performed for each of African and Asian ancestries (8,9). Replication studies for variants discovered in European populations have also been performed in these populations (22)(23)(24)(25)(26)(27)(28). The 10q, 17q, and Xp variants (rs10993994, rs4430796, and rs5945619) are associated with PCa risk in men of European, Japanese, and African ancestries (8,(23)(24)(25), and these polymorphisms are also associated with MSMB, NCOA4, HNF1B, and NUDT11 transcripts across all three ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additional markers have been reported to be associated with prostate cancer at 8q24 particularly in men of African descent that were not originally identified in GWAS based in European populations. These include rs7008482 (11,14,16), rs4871005 (11,14), rs6981122 (11,14), and bd11934905 (21,26,51). These markers also hold promise for further study of clinical utility in prostate cancer risk assessment.…”
Section: Discussionmentioning
confidence: 99%